Walkability, accessibility to metro stations and retail location choice: Some evidence from the case study of Naples. (September 2021) - Tinessa, Fiore; Pagliara, Francesca; Biggiero, Luigi; Delli Veneri, Giorgia
Abstract: Retail location choice and transportation systems are strictly dependent on each other. If, from one hand, the former has clear effects on the latter (being one of the determinants of travel demand), it is interesting to assess also the reverse impact. In this respect, notwithstanding the impact of accessibility to metro stations has been investigated in previous literature, few studies have highlighted the effect of active travel modes on retail location choice, so as no previous study has analysed this impact at a disaggregate level through a Stated Preference (SP) survey. This paper focuses on the choice behaviour of single retailers / managers of three densest urban retail districts in the city of Naples (in the South of Italy). The work analysis the impact of walkability and accessibility to metro stations on retail / businesses location choice. A SP survey and the estimation of several random utility models (RUM) have been carried out, with the aim of evaluating the distribution of retailers' Willingness To Pay (WTP). Results show that retailers are more willing to pay for locating their activities close to pedestrian zones rather than metro stations and provides other insights on the effect of socio-demographic variables.